2013
DOI: 10.1016/j.bbrc.2012.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Proteins contribute insignificantly to the intrinsic buffering capacity of yeast cytoplasm

Abstract: Intracellular pH is maintained by a combination of the passive buffering of cytoplasmic dissociable compounds and several active systems. Over the years, a large portion of and possibly most of the cell's intrinsic (i.e., passive non-bicarbonate) buffering effect was attributed to proteins, both in higher organisms and in yeast. This attribution was not surprising, given that the concentration of proteins with multiple protonable/deprotonable groups in the cell exceeds the concentration of free protons by a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Finally, we comment on the estimated phosphate concentration (160–320 mM; see Table S3 ), which is obtained from fitting of the pH kinetics in vivo. Although this value is larger than the estimated 41 mM intrinsic buffering capacity of a yeast cytosol extract ( 30 ), our value is in good agreement with the total phosphorus concentration of ∼300 mM in yeast (free + bound phosphate groups, organic phosphates, polyphosphate) ( 27 ). We assume that phosphate present in metabolic intermediates (e.g., sugar phosphates) and bound to proteins contributes to the overall buffering, similar to inorganic phosphate; the pKa value of phosphate in sugar phosphates is similar to that of inorganic phosphate.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Finally, we comment on the estimated phosphate concentration (160–320 mM; see Table S3 ), which is obtained from fitting of the pH kinetics in vivo. Although this value is larger than the estimated 41 mM intrinsic buffering capacity of a yeast cytosol extract ( 30 ), our value is in good agreement with the total phosphorus concentration of ∼300 mM in yeast (free + bound phosphate groups, organic phosphates, polyphosphate) ( 27 ). We assume that phosphate present in metabolic intermediates (e.g., sugar phosphates) and bound to proteins contributes to the overall buffering, similar to inorganic phosphate; the pKa value of phosphate in sugar phosphates is similar to that of inorganic phosphate.…”
Section: Resultssupporting
confidence: 81%
“…The relevant pKa value of CO 2 (aq) is 6.73. We set the pKa of KPi to the pKa of the yeast cytosol as measured in ( 30 ). The external solution, at pH 6, contains 100 mM KPi and 11.3 μ M of CO 2 (aq).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the buffering capacity of the protein itself is negligible both in vitro ( Kirkwood et al. , 2014 ) and in vivo ( Poznanski et al. , 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exchangers can exploit the energy stored in pH gradients to transport ions and solutes against a gradient or to assist in pH control using the gradient of another ion, and may represent the source of the “proton leak” that helps to determine final pH in various organelles [10]. Buffers, particularly the robust phosphate buffering system in S. cerevisiae [11], protect cells and organelles from short-term pH transients, but cannot withstand long-term shifts without assistance from proton transporters [9]. …”
Section: The Physiological Context Of Ph Homeostasis In S Cerevisiaementioning
confidence: 99%